Development of new therapeutic strategies for siRNA delivery - Pereira, Patrícia Alexandra Nunes (2011)
The importance of RNA in numerous biological processes has increased substantially over recent years. Small RNAs (sRNAs) are increasingly recognized as crucial regulatory molecules in all organisms and the specificity and potency of small RNAs suggest that they might be promising as therapeutic agents, namely in interference RNA strategies. These strategies generally rely on the use of synthetic siRNA. Although the synthesis of siRNA can be very efficient, the oligonucleotides typically present contaminants, which leads to the need for the development of new processes for the production of highly purified and clinically suitable siRNA oligonucleotides for use in therapy. Rhodovulum sulfidophilum have the ability to produce active extracellular sRNA; therefore, the potential use of this organism to obtain functional recombinant sRNA with large therapeutic applicability is eminent. However, the success of sRNA therapies depends upon the ability to selectively and efficiently deliver therapeutic sRNA to target organ with minimal toxicity. For this purpose, novel nanodevices and vehicles have been formulated with materials that possess ideal intrinsic transfection and unpacking characteristics. In order to optimize the production of Rhodovulum sulfidophilum DSM 1374 extracellular sRNAs, the influence of temperature and NaCl concentration on the specific growth rate and in extracellular sRNA production were evaluated. The experiments performed showed that the aerobic cultivation in the dark, with nutrient broth medium containing 3 % NaCl at 30 ºC, conducted to a maximum production of extracellular sRNAs yielding 197 ± 0.55 Mg/mL. For the improvement of the biological effect in RNAi-based therapies, the design and synthesis of optimal non-viral vectors for sRNA delivery, using commercial polymers, such as Polyethylenimine, Chitosan and Poly(allylamine) were performed. The results obtained showed that the structural and physicochemical properties (size, zeta potential and morphology) of the nanoparticles are strongly dependent on polycation molecular weight, charge density and structure, and also on the formulation ratio of amine to phosphate groups present in the RNA (N/P ratio) and, ultimately, alterations in these parameters influence the association efficiency and stability of sRNA. Overall, the implementation of this cutting-edge approach provides the basis for the future development of effective sRNA-based gene therapy applications.